Knowledge and Attitude of Cadres in the Prevention and Treatment of Diarrhea At Home Among Mothers of Toddlers - Haryani, Sri; Yusniarita, Yusniarita; Sutriyanti, Yanti; Bakara, Derison Marsinova (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the knowledge and attitudes of cadres in preventing and treating diarrhea at home among mothers who have toddlers at home. This research uses a quantitative type of research with a Quasi Experimental design in the intervention and control groups. The design used is pre-test and post-test. The results of the research showed that pre-test knowledge for the intervention and control groups was cadres aged 57 years (95%), adults, 59 people (98.3%) had higher education, 44 people (73.3%) had been a cadre for a long time. Pre knowledge with pvalue 0.257, post pvalue 0.000 and attitude pre pvalue 0.379 post pvalue 0.160. The conclusion, was that cadres' knowledge was good after health education and cadres' attitudes were poor after health education in preventing and treating diarrhea at home for mothers with toddlers. Keywords: Knowledge, Attitude, Cadre, Prevention, Treatment, Diarrhea